Prevalence of Panic Disorder and Associated Factors among Nurses Working in Covid-19 Isolation Centres in Lagos, Nigeria - Rasheed, Tajudeen Olusegun; Aina, Joseph Oyeniyi (European Journal of Applied Sciences, 2022)
Nurses suffered panic disorder due to virulent high aerosol spreading rate of coronavirus and limited data on definitive treatment of affected COVID-19 patients. This study assessed the prevalence of panic disorder and associated factors among nurses working in COVID-19 isolation centres in Lagos, Nigeria. The study was a quantitative, cross-sectional survey design. A population of N=75 nurses was sampled using a total enumeration sampling technique. Purposive sampling method was used to select the two isolation centres where the study was conducted. A structured self-administered questionnaire with validity and reliability established was used to collect data from nurses between 7th February and 25th March, 2022. Data were collated, screened and imported into SPSS version 25 for analysis. Significance levels of associated factors were established with Fisher’s Exact Test and Multivariate Logistic Regressions at significant level of p < 0.05 and 95% confidence interval. The results showed the mean age of nurses was m=37.6 + 10.2 years and 20.6% developed panic disorder. The age p=0.002, and living with vulnerable persons p=0.005 were significantly associated with panic disorder p < 0.05. Nurses who felt there is threat to their life working in COVID-19 isolation centre were 3.4 times more likely to develop panic disorder compared to nurses who did not (AOR=3.4, 95% CI=2.337, 7.271, p=0.001). In conclusion, twenty percent of nurses developed mild to severe panic disorder due to associated psychological and working conditions factors. Counseling and support program is recommended for affected nurses to improve quality of life.